A Unique Case of Central Venous Sinus Thrombosis in Type 2 Diabetes with Severe Hypertriglyceridemia - Sanyal, Debmalya; Bhattacharjee, Kingshuk; Chaudhuri, Soumyabrata Roy (Bangladesh Critical Care Journal, 2016)
We present a case of superior sagittal sinus thrombosis caused by uncontrolled type 2-diabetes and extremely high triglyceride. We believe this is the first report that demonstrates an association of CVST with uncontrolled type-2-diabetes and hypertriglyceridemia in an adult but in the absence of concomitant ketoacidosis, hyperosmolar state or any known pro-thrombotic conditions. Our case highlights the need for clinicians to consider CVST among patients with uncontrolled diabetes and hypertriglyceridemia. New diagnostic measures may become necessary which may also have an implication on the risk of recurrence and duration of anti-coagulant therapy in this group of patients. Bangladesh Crit Care J March 2016; 4 (1): 58-60